2013
DOI: 10.1016/j.leukres.2013.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical, pharmacokinetic, and pharmacodynamic study of the Akt-inhibitor triciribine phosphate monohydrate in patients with advanced hematologic malignancies

Abstract: Akt, a serine/threonine protein kinase, is constitutively phosphorylated and hyperactivated in multiple cancers, including acute myeloid leukemia. High levels are linked to poor survival and inferior responses to chemotherapy, making Akt inhibition an attractive therapeutic target. In this phase I/II study of TCN-PM, a small-molecule Akt inhibitor, TCN-PM therapy was well tolerated in patients with advanced hematological malignancies, and reduced levels of phosphorylation of Akt and its substrate Bad were show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Akt is important for a wide range of cellular functions and interacts with an immense number of substrates [52]. Only a few Akt inhibitors have been developed, and they have not produced convincing effects in AML [131,132]. Results from selected representative and relatively large clinical studies of PI3K-Akt-mTOR inhibitors were recently reviewed by Herscbein and Liesveld [133], and Table 1 represents the most relevant studies.…”
Section: Inhibition Of the Pi3k-akt-mtor Pathway In Amlmentioning
confidence: 99%
“…Akt is important for a wide range of cellular functions and interacts with an immense number of substrates [52]. Only a few Akt inhibitors have been developed, and they have not produced convincing effects in AML [131,132]. Results from selected representative and relatively large clinical studies of PI3K-Akt-mTOR inhibitors were recently reviewed by Herscbein and Liesveld [133], and Table 1 represents the most relevant studies.…”
Section: Inhibition Of the Pi3k-akt-mtor Pathway In Amlmentioning
confidence: 99%
“…The treatment had an acceptable toxicity profile and correlative studies demonstrated a significant reduction in the levels of pAKT (Ser473) and pBAD (Ser112). 52 While no objective responses were documented, stable disease among 17 patients suggested a potential role for this inhibitor. 52 The phospholipid analog, perifosine, inhibits AKT by altering lipid rafts and preventing the membrane localization of AKT, resulting in apoptosis of AML cell lines and enhancement of etoposide cytotoxicity.…”
Section: Aktmentioning
confidence: 98%
“…52 While no objective responses were documented, stable disease among 17 patients suggested a potential role for this inhibitor. 52 The phospholipid analog, perifosine, inhibits AKT by altering lipid rafts and preventing the membrane localization of AKT, resulting in apoptosis of AML cell lines and enhancement of etoposide cytotoxicity. 53 These results provided the impetus for ongoing clinical studies of perifosine in refractory AML and other malignancies (NCT00391560).…”
Section: Aktmentioning
confidence: 98%
See 1 more Smart Citation
“…Akt is important for a wide range of cellular functions and interacts with an immense number of substrates [122]. Only a few Akt inhibitors have been developed, and they have not produced convincing effects in AML [187,188]. ___________________________________________________________________________ Results from selected representative and relatively large clinical studies of PI3K-Akt-mTOR inhibitors were recently reviewed by Herscbein-Liesveld and colleagues [189] and Table 3 represents the most relevant studies.…”
Section: Pi3k-akt-mtor and Ras-raf-mek-erk Pathway Cross Talkmentioning
confidence: 99%